Истоки: [альманах / редколлегия: С. Рыбас и др.] - Рыбас Святослав Юрьевич (Стихи и проза молодых, 1990)
Экземпляры: КХ (20180703) / Инвентарный номер: 958051 / Сис.шифр: Р2 / Авт.знак: И 89 / ГРНТИ: 17 / ББК: 84(2)